The Practice of Learning Management System (LMS) in Teaching Speaking - Titik Ismailia (Politeknik Negeri Jember, 2022)
This study aims to look over the use of the Learning Management System (LMS) in teaching speaking for the Basic English course. The subject of the research is the first-semester students of Mechatronics Engineering. This paper will apply descriptive qualitative research. The data will take from a survey of 76 students to know the practice of LMS in teaching speaking. The result shows that the speaking material that has been uploaded is useful for students to understand the topic. Moreover, the features in LMS Moodle such as downloading materials, submitting assignments, and quizzes are easy to operate so that teaching-learning through LMS can run well. The LMS also helps the teacher to be creative in designing the materials for teaching to make the students do the task better.